Validation of weight estimation by age and length based methods in the South African population - Geduld, Heike (Division of Emergency Medicine, 2017)
Paediatric resuscitation can be a stressful event for many clinicians. It is compounded by the need to calculate accurate drug dosages and equipment sizes for many interventions. These calculations are most often based on weight, which is a difficult parameter to obtain. It is rare that one is able to weigh a child before a resuscitation. There are many different methods available for weight estimation. Most of these are formulae based on age but length based tools are often used. Most of these formulae were derived in developed world populations and have become inaccurate due to the changing weights and heights of children. The aim of this study was to evaluate 4 weight estimation methods (APLS, Luscombe and Owens, Best Guess and Broselow® Tape) to determine which are accurate for weight estimation in South African Children. These 4 formulae were also used to calculate the doses of adrenaline (0.1 m/kg of 1: 10000), Fluid bolus (20ml/kg) and First Shock defibrillation dose (2J/Kg) to determine which were clinically useful. A database of 3233 children between 1 and 12 years seen at Red Cross Hospital· Trauma Unit in Cape Town during 2002 was used. Measured weight was compared to estimated weights from all 4 methods and Intervention doses calculated from measured weight was compared to doses from weight estimation methods. APLS formula and the Broselow® Tape showed the best correlation with measured weight. Mean percent error- 6.4% for APLS for 1-10 year olds and -10% error for Broselow® tape in children <145cm length. Both the Best Guess and Luscombe and Owens formulae tended to overestimate weight (+13.4% and +17.6 % respectively). The Broselow tape was most accurate for dosages of all interventions but little difference existed between methods. The APLS and Broselow® tape are most accurate in estimating weight in the South African population, even though they have a tendency to underestimate weight.